1996
DOI: 10.1021/ma9600062
|View full text |Cite
|
Sign up to set email alerts
|

Phase Behavior of Agarose in Binary Solvents

Abstract: The thermoreversible gelation of agarose has been investigated in four different aqueous binary solvents: water/dimethyl sulfoxide, water/N,N-dimethylformamide, water/N-methylformamide, and water/formamide. The thermal behavior through the gelation/melting temperatures and the gelation/ melting enthalpies has been studied, and phase diagrams have been subsequently established as a function of agarose concentration and solvent composition. The elastic modulus has been determined as a function of the same parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 12 publications
1
27
0
Order By: Relevance
“…The substitution of the single chain with the double chain model decreases significantly the mobility of agarose, as the rms fluctuation with respect to its backbone drops from 10 Å in the case of the single chain to about 4 Å for the double chain. The double chain agarose structural model here proposed is based on the available literature evidence and in particular on the seminal works of Arnott et al (55), who initially proposed that agarose is formed by bundles of double helixes, left handed, with a helix pitch of 26 Å, and on the successive works of Ramzi et al (56, 57) and, more recently, of Xiong et al (58), who suggested that agarose should be thought of as a random assembly of straight fibers. Clearly, a fiber will be formed by more than a set of two double helixes.…”
Section: Resultsmentioning
confidence: 99%
“…The substitution of the single chain with the double chain model decreases significantly the mobility of agarose, as the rms fluctuation with respect to its backbone drops from 10 Å in the case of the single chain to about 4 Å for the double chain. The double chain agarose structural model here proposed is based on the available literature evidence and in particular on the seminal works of Arnott et al (55), who initially proposed that agarose is formed by bundles of double helixes, left handed, with a helix pitch of 26 Å, and on the successive works of Ramzi et al (56, 57) and, more recently, of Xiong et al (58), who suggested that agarose should be thought of as a random assembly of straight fibers. Clearly, a fiber will be formed by more than a set of two double helixes.…”
Section: Resultsmentioning
confidence: 99%
“…This mechanism was previously suggested by different authors (Anderson et al , 1969; Arnott et al , 1974), suggesting that the occurrence of double helices during cooling was responsible for the aggregation that produces the 3D hydrogel network, due to hydrogen bonding and hydrophobic interactions. Nevertheless, other studies have suggested that single chain formation would enable gel formation (Foord et al , 1989; Guenet et al , 1993) or the assembly of ternary complexes consisting of agarose–water–co‐solvent would lead to the same structure (Ramzi et al , 1996). The melting of agarose gels can occur at higher temperatures, normally around 85 °C (Normand et al , 2000).…”
Section: Polysaccharides In Cartilage Tissue Engineeringmentioning
confidence: 99%
“…This process should affect markedly the gel mechanical properties such as the magnitude of the elastic modulus which is directly linked to the concentration of the agaroserich phase and to its rigidity. Yet, altering the composition of the binary solvent is seen to have no significant effect on the elastic modulus (Ref 8)…”
mentioning
confidence: 99%